Improving the Mongolian labor market and enhancing opportunities for youth - Shatz, Howard J.; Constant, Louay; Pérez Arce, Francisco; Robinson, Eric (Policy analyst); Beckman, Robin L.; Huang, Haijing; Glick, Peter; Ghosh-Dastidar, Bonnie (Research report (Rand Corporation), 2015)
"Despite a recent slowdown, Mongolia has experienced dramatic economic growth in the 2000s, exceeding global trends. Foreign direct investment, mining, infrastructure spending, and, more recently, strong fiscal and monetary stimulus measures have driven much of this growth. The country now faces challenges in terms of creating jobs without overly relying on public spending fueled by natural resource exploitation. In 2014, the Mongolian government commissioned RAND to collaborate on a study of the labor market with the Institute for Labour Studies (ILS) of the Mongolian Ministry of Labour. Using a supply-demand framework, this study analyzed the Mongolian labor market to identify where it is performing well, where it is underperforming, and whether there are constraints to improvement. RAND and ILS especially focused on youth labor and education issues, using a new survey developed by the two organizations. The ILS and RAND teams chose this focus because of the importance of youth labor-market success to the economic future of the country and because analysis of Mongolian labor data showed relatively high rates of youth not in school or the labor market compared with a variety of other economies, including other similar transition economies. The Mongolian Ministry of Population Development and Social Welfare has recognized this importance by announcing 2015 as the year of youth development. The ILS-RAND Mongolian Youth Survey is a nationwide survey that provides new insights into the challenges faced by youth, as well as their achievements and aspirations, to inform the development of policy to address these concerns."--Back cover